2016
DOI: 10.1159/000447132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Lidocaine versus a Lidocaine-Bupivacaine Combination in a Periprostatic Nerve Block Undergoing Transrectal Ultrasound-Guided Prostate Biopsy: A Double-Blind Randomized Controlled Trial

Abstract: Introduction: To determine whether a combination of the long acting local anesthetic, bupivacaine, and lidocaine is better than lidocaine alone in the long-term pain control, which is a short-acting anesthetic. Materials and Methods: In group 1, periprostatic nerve block was applied to both neurovascular areas with 2% lidocaine (5 ml) in an isotonic solution (5 ml). In group 2, the combination of 2% lidocaine (5 ml) and 5mg/ml bupivacaine (5 ml) was used for the PPNB. Results: In the first 30 minutes the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…34 Prospective double-blinded study in urologic patients demonstrated that a combination of lidocaine and bupivacaine was associated with significantly lower patient-reported pain scores at 1, 2, 4, 6, and 8 h postoperatively. 35 Another urologic study demonstrated that patients receiving the combination of bupivacaine and lidocaine experienced significantly less pain every subsequent day after their procedure. 36 Patients undergoing cleft lip surgery are usually admitted postoperatively and are discharged on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…34 Prospective double-blinded study in urologic patients demonstrated that a combination of lidocaine and bupivacaine was associated with significantly lower patient-reported pain scores at 1, 2, 4, 6, and 8 h postoperatively. 35 Another urologic study demonstrated that patients receiving the combination of bupivacaine and lidocaine experienced significantly less pain every subsequent day after their procedure. 36 Patients undergoing cleft lip surgery are usually admitted postoperatively and are discharged on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Although transrectal ultrasound-guided (TRUS) prostatic biopsy has been considered a minor procedure, people often experience pain, anxiety and disturbances before, during and after the procedure [7]. About 65–90% of men experience pain based on different factors: entering an ultrasound probe in the rectum, the movement of this device, size and geometry of the probe, the insertion of the needle for injecting anesthetics, the biopsy itself, among others [6, 7, 8].…”
Section: Introductionmentioning
confidence: 99%